2022
DOI: 10.1186/s40479-022-00203-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a skills-based peer-led art therapy online-group for people with emotion dysregulation

Abstract: Objective We developed and piloted a novel art-based online skills program led by a peer mental health professional with lived experience of complex mental health, including Borderline Personality Disorder (BPD). Key challenges of living with BPD and emotion dysregulation were addressed through artmaking informed by a dialectical framework and skills, to evaluate acceptability and efficacy. Method A structured, manualised 2-hour weekly arts-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 62 publications
0
10
0
6
Order By: Relevance
“…The themes identified in the feedback from peer group participants align with the extant literature regarding benefits of peer support for people with serious mental illness, specifically social support, empowerment, increased self‐efficacy, and promotion of self‐management (Repper & Carter, 2011), and demonstrated that this is also achievable for people diagnosed with BPD in a group setting. The findings parallel qualitative feedback in the evaluation of a skills‐based peer‐led art group for people with difficulties in emotional regulation and BPD, in which participants reported benefits in being able to be vulnerable and connected with others, with the role of peer facilitation bringing authenticity to the experience (Jewell et al, 2022). Our findings emphasized how a peer‐led group helped people to feel safe and overcome some of the barriers that may be perceived in clinical settings, given consumers may be less concerned about power dynamics when interacting with peer workers (Barr et al, 2022).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…The themes identified in the feedback from peer group participants align with the extant literature regarding benefits of peer support for people with serious mental illness, specifically social support, empowerment, increased self‐efficacy, and promotion of self‐management (Repper & Carter, 2011), and demonstrated that this is also achievable for people diagnosed with BPD in a group setting. The findings parallel qualitative feedback in the evaluation of a skills‐based peer‐led art group for people with difficulties in emotional regulation and BPD, in which participants reported benefits in being able to be vulnerable and connected with others, with the role of peer facilitation bringing authenticity to the experience (Jewell et al, 2022). Our findings emphasized how a peer‐led group helped people to feel safe and overcome some of the barriers that may be perceived in clinical settings, given consumers may be less concerned about power dynamics when interacting with peer workers (Barr et al, 2022).…”
Section: Discussionmentioning
confidence: 55%
“…Similar to Jewell et al (2022), integrating creative activities into the group structure was important and may increase treatment engagement for people who find traditional therapeutic environments overwhelming or a poor fit to their needs. The literature suggests that while some people with borderline symptoms go on to achieve personal recovery (stable functioning with good interpersonal relationships, self-worth, and vocational functioning), those that do not improve over time may benefit from programmes that specifically focus on activities of daily living and interpersonal relationships (Grenyer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lived experience perspectives have been important in previous studies to broaden the concept of ‘recovery’ and the importance of ‘love and work’ goals for individuals with BPD (Grenyer et al, 2022; Ng et al, 2016; Ng, Carter, et al, 2019). Similarly, lived experience has also been meaningfully incorporated into health service delivery, either through encouraging service redesign (Barr, Jewell, et al, 2020) or through peer‐led interventions (Barr, Townsend, & Grenyer, 2020; Jewell et al, 2022). However, in terms of receiving a diagnosis of BPD, lived experience perspectives are somewhat scant.…”
Section: Introductionmentioning
confidence: 99%